Risiko Perkembangan Teknologi Perbankan Syariah Era Millenial - Muhlis Masin; Asyraf Mustamin; Farid Fajrin; Supriadi Supriadi; Trisno Wardy Putra; Trimulato Trimulato (Al-Azhar Journal of Islamic Economics, 2022)
The risk that have been faced by sharia financial institution is not merely about financial issue but also non-financial. Hence, it is considered as an urgency to be able to implement the risk management in order to conduct the hedging strategy in sharia financial institution, and also to anticipate and ready for further action needed in facing some irrelevant situations which are not according with the expectations and the objectives of the institution. This writing aims to assess the risk management in identifying and in managing of that.  However, because of the complexity of the risk encountered both in financial and non-financial issue; such as operational risk of the use of modern technology services which does increasingly pamper the current millennial clients and that prone to cyber-security threat and thus needs protection. Also economic uncertainty with the state of pandemic covid 19.